Edible insects contributing to food security?. Issue 1 (December 2015) - van Huis, Arnold
Abstract Because of growing demand for meat and declining availability of agricultural land, there is an urgent need to find alternative protein sources. Edible insects can be produced with less environmental impact than livestock. Insect meal can replace scarce fishmeal as feed ingredient, in particular in the fast growing aquaculture industry. Edible insects can alleviate waste disposal problems by growing them on organic by-products. About 2000 insect species are eaten worldwide, mostly in tropical countries. They have adequate protein quantity and quality and high content of unsaturated fatty acids and minerals like iron and zinc. Promotion of insects as food and feed will require the insects to be farmed. In tropical countries this is done small-scale, but in particular for use of insects as feed, production is needed in large automated industrial facilities. Food safety problems relate to contamination with pathogens, requiring hygienic farming. Proper labelling may be required for people allergic to seafood and house dust mites as cross reactivity may occur. Western consumers are hard to convince to eat insects, even when aware of environmental, nutritional and food safety benefits and their excellent taste. Emotional and psychological impediments to acceptance have to be addressed. The way forward of edible insects to become a new sector in agriculture and the food and feed industry is discussed. In particular, legislation lags behind developments and needs to be addressed urgently.